Effectiveness of Virtual Reality in Enhancing Social Empathy through Historical Event Simulations - Difa'iy Aziz, Muhandis (PT. Anagata Sembagi Education, 2025)
Virtual reality (VR) technology has emerged as a promising tool for enhancing social empathy through immersive historical event simulations. However, empirical evidence regarding its effectiveness compared to traditional learning methods remains limited. This study aims to examine the effectiveness of VR-based historical event simulations in enhancing social empathy compared to traditional narrative-based learning methods. A randomized controlled trial was conducted with 120 undergraduate students randomly assigned to three groups: VR simulation group (n=40), traditional video-based learning group (n=40), and control group (n=40). The intervention involved experiencing historical events related to social injustice. Social empathy was measured using the Interpersonal Reactivity Index (IRI) and Jefferson Scale of Empathy (JSE) before and after intervention. Data were analyzed using SPSS 26 with repeated measures ANOVA and post-hoc tests. VR group showed significantly higher improvements in emotional empathy scores (M=42.15, SD=5.23) compared to video group (M=36.82, SD=4.76) and control group (M=31.47, SD=4.19), F(2,117)=58.74, p<0.001, η²=0.501. However, no significant differences were found in cognitive empathy scores between VR and video groups (p=0.127). The effect size for VR intervention on overall empathy was large (Cohen's d=1.24). VR-based historical event simulations effectively enhance emotional empathy but show limited impact on cognitive empathy. These findings suggest VR's potential as a complementary educational tool while highlighting the need for integrated approaches in empathy education.